Deep eutectic gel electrolyte and preparation method and application thereof
Through the preparation of electrolyte electrolytes of deep -co -chip gel, the combination of hydrogen bonds and hydrogen bond receptors to form a polymer network, solving the problem of mechanical performance, conductivity and stability of traditional electrolyte materials, and achieve high safety, high stability , Lifetime lithium/sodium battery system.
Patent Information
- Application Number
- CN202411440482.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-15
AI Technical Summary
Among the existing battery materials, traditional liquid electrolytes have problems such as high volatility, flammability, and strong leakage. Solid electrolytes such as PEO-based polymer electrolytes show limited mechanical properties, low oxidation potential, narrow voltage window and poor The room temperature ionic conductivity limits its practical application.
Using a deep -compulsory crystal gel electrolyte, a polymer network is formed through the combination of hydrogen bonding body and hydrogen bond receptor, and a polymer network is prepared to prepare high ionic conductivity, wide -electrochemical stable window, good mechanical performance and good compatibility and metal metal The electrolyte of the deep co -crystal gel of theode.
The quasi -solid -lithium/sodium battery system with high security, high stability, and long life has a high -ion conductivity, wide -electrochemical stability window and good mechanical properties. It is suitable for large -scale energy storage applications.
Smart Images

Figure BDA0005086233200000061 
Figure BDA0005086233200000071 
Figure HDA0005086233250000011
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery materials, and in particular to a deep eutectic gel electrolyte, a preparation method thereof, and applications thereof. Background Art
[0002] As a platform for ion transport, electrolyte is one of the key components of batteries. Traditional liquid electrolytes are limited by high volatility, flammability, strong leakage, dendrites and other problems. Replacing liquid electrolytes with solid electrolytes is expected to solve safety issues. Among them, polyethylene oxide (PEO)-based polymer electrolytes are considered to be the most promising electrolyte materials due to their excellent chemical stability and high solubility in sodium salts. However, PEO-based electrolytes exhibit limited mechanical properties, low oxidation potential, narrow voltage window (<4.0V) and poor room temperature ionic conductivity (≈10 -3 mxD -1 ), which greatly limits their practical applications (Adv. Energy Mater, 2018, 17, 1703012). Su et al. designed a new polymer composed of β-cyclodextrin (β-CD) and poly(trifluoroethyl methacrylate) (PTFEMA), and blended it with PEO to prepare a PEO-based all-solid polymer. The conductivity of the polymer at 25°C is 2.59×10 -3 mxD -1 (Nat. Commun., 2022, 13, 4181). Compared with PEO, polyvinylidene fluoride (PVDF) has better thermal stability, electrochemical stability and mechanical properties. However, as a semi-crystalline polymer, PVDF has high crystallinity, small amorphous region and poor ion conductivity (ACS Appl. Mater. Interfaces, 2021, 13, 35664-35676). The team of Academician Nan Cewen has Li 6.75 La 3 Zr 1.75 Ta 0.25 O 12 After the (LLZTO) filler was introduced into the PVDF matrix, the polymer underwent a dehydrofluorination reaction, thereby enhancing the interaction between the PVDF matrix, lithium salt and LLZTO. The conductivity of this composite solid electrolyte at 25°C was 0.5 mS cm -1 (J.Am.Chem.Soc.,2017,139,13779-13785). The above polymer electrolytes generally have the disadvantages of high interfacial resistance and low ionic conductivity.
[0003] Quasi-solid gel electrolytes, as an intermediate state between liquid electrolytes and solid electrolytes, have attracted widespread attention due to their good ionic conductivity and excellent compatibility with electrodes at room temperature. Traditional gel polymer electrolytes, which usually use high molecular weight polymers as a skeleton and are loaded with flammable solvents such as carbonates, still have great safety risks.
[0004] Deep eutectic solvents (also known as low eutectic solvents) are low melting point mixtures obtained by complexing hydrogen bond donors and hydrogen bond acceptors. They have the advantages of being non-flammable and simple to prepare. Currently, there are few reports on deep eutectic gel electrolytes (or low eutectic gel electrolytes) suitable for sodium ion batteries and lithium ion batteries. The invention patent with patent number CN202310534520.X reports a method for in-situ polymerization of gel electrolytes in a low eutectic solvent system, using acrylic acid (ester) or acrylamide compounds as hydrogen bond donors; at least one of imidazolium-based ionic liquids, pyrrolyl-based ionic liquids and pyridine-based ionic liquids as hydrogen bond acceptors, and a low eutectic gel electrolyte is prepared by in situ polymerization; the ionic conductivity of the gel electrolyte in this system is 1.5 mS cm -1 The above are mainly used in lithium-ion batteries. There is no research report on deep eutectic gel electrolytes that use alkali metal salts as hydrogen bond acceptors and unsaturated double bond monomers as hydrogen bond donors as raw materials, and that simultaneously meet the requirements of a wide electrochemical stability window, good mechanical properties, and high conductivity. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a deep eutectic gel electrolyte and its application. The electrolyte is easy to prepare, has high ionic conductivity and a wide voltage window, and has good mechanical properties. It has good compatibility with the metal anode interface and can effectively inhibit the growth of dendrites. A highly safe, highly stable, and long-life quasi-solid-state lithium / sodium battery system is constructed, providing a feasible solution for large-scale energy storage.
[0006] In order to achieve the above object, the present invention particularly adopts the following technical solutions:
[0007] The first aspect of the present invention provides a polymerizable deep eutectic solvent for preparing a gel electrolyte, wherein the preparation raw materials include: a hydrogen bond donor and a hydrogen bond acceptor, wherein the hydrogen bond donor contains an amide monomer having an unsaturated double bond.
[0008] Preferably, the amide monomer is one or more of acrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, N-isopropylacrylamide, and 4-acryloylmorpholine.
[0009] Preferably, the hydrogen bond acceptor includes sodium hexafluorophosphate, sodium perchlorate, sodium bis(trifluoromethanesulfonyl imide), sodium bis(fluorosulfonyl imide), sodium tetrafluoroborate, sodium trifluoromethanesulfonate, sodium nitrate, lithium perchlorate, lithium nitrate, lithium bis(trifluoromethanesulfonyl imide), and lithium bis(fluorosulfonyl imide).
[0010] Preferably, the molar ratio between the hydrogen bond acceptor and the hydrogen bond donor is 1:0.2 to 1:15.
[0011] The second aspect of the present invention provides a deep eutectic gel electrolyte, comprising the following raw material components which are stored independently: the polymerizable deep eutectic solvent as described in the first aspect, and also comprising additives and initiators.
[0012] The additive is a film-forming additive, preferably fluoroethylene carbonate (FEC). FEC can form a thin film covering the surface of the negative electrode, effectively preventing the side reaction between the electrolyte and the negative electrode, and further improving the battery cycle life.
[0013] Preferably, the initiator is a free radical initiator; including one or more of 2-oxoglutaric acid, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (also known as 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone), and azobisisobutyronitrile. The third aspect of the present invention provides a method for preparing the above-mentioned deep eutectic gel electrolyte, comprising the following steps:
[0014] Step 1: mixing the hydrogen bond acceptor and the hydrogen bond donor in a certain molar ratio, and stirring at a certain temperature until the mixture becomes clear and transparent, thereby obtaining a polymerizable deep eutectic solvent;
[0015] Step 2: adding a certain amount of additives and initiator to the solution prepared in step 1 and mixing them evenly to obtain a prepolymer solution;
[0016] Step 3: Pour the prepolymer solution obtained in step 2 into a mold, and then initiate polymerization under light or heating conditions to obtain a deep eutectic gel electrolyte.
[0017] Preferably, the polymerization condition in step 3 is polymerization under ultraviolet light conditions, and the ultraviolet curing reaction time is determined by the corresponding polymerization reaction and light power.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] 1. The preparation method of the deep eutectic gel electrolyte provided by the present invention generates a hydrogen bond network between polymers formed by hydrogen bond acceptors and hydrogen bond donors. The gel electrolyte has excellent interface adhesion, good mechanical properties and high ionic conductivity at room temperature.
[0020] 2. The deep eutectic gel electrolyte provided by the present invention utilizes polymerizable monomers as hydrogen bond donors. The polymer chain segments formed after the monomers are polymerized have high antioxidant properties, which broadens the electrochemical window of the gel electrolyte. At the same time, the steric hindrance generated by the polymer chain segments inhibits the side reactions between the alkali metal and succinonitrile, so that the assembled symmetrical batteries and full batteries have good cycle stability.
[0021] 3. The preparation method of the deep eutectic gel electrolyte provided by the present invention is simple, easy to operate, has good repeatability, short time consumption, is suitable for large-scale production, and has industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 . Photo of the polymerizable monomeric deep eutectic solvent prepared in Example 1
[0023] Figure 2 . Photo of the deep eutectic gel electrolyte prepared in Example 2
[0024] Figure 3 . LSV of deep eutectic gel electrolyte prepared by homopolymerization of different monomers in Example 3
[0025] Figure 4 . LSV of deep eutectic gel electrolyte prepared by copolymerization of different monomers in Example 4
[0026] Figure 5 . Stress-strain diagram of the deep eutectic gel electrolyte prepared in Example 4
[0027] Figure 6 . Voltage-time curve of the Na / / Na symmetric battery assembled with deep eutectic gel electrolyte at room temperature for deposition / stripping charge-discharge cycles in Example 4
[0028] Figure 7 EIS curves of the Na / / Na symmetric battery assembled with deep eutectic gel electrolyte in Example 4 before and after 1000 cycles
[0029] Figure 8 EIS curve of deep eutectic gel electrolyte prepared from lithium salt in Example 5 at room temperature
[0030] Fig. 9 LSV of the deep eutectic gel electrolyte prepared from lithium salt in Example 5
[0031] Fig.10 . Voltage-time curve of the Na / / Na symmetric cell assembled in Example 6 during deposition / stripping charge-discharge cycles at room temperature
[0032] Fig.11CV curve of HQ-NaFe / / Na battery assembled in Example 7
[0033] Fig.12 .CV curve of NFM / / Na battery assembled in Example 8
[0034] Fig.13 . CV curve of NVP / / Na battery assembled in Example 9
[0035] Fig.14 GCD curves of the NVP / / Na battery assembled in Example 9 at different current densities
[0036] Fig.15 Example 9 Comparison of the cycling performance of NVP / / Na batteries assembled with gel electrolyte and liquid electrolyte at 1C
[0037] Fig.16 . CV curve of LFP / / Li battery assembled in Example 10 DETAILED DESCRIPTION
[0038] The drawings of the present invention are only used for illustrative purposes and are not to be construed as limiting the present invention.
[0039] The present invention will be described in detail below by way of examples. The following examples are intended to illustrate the present invention rather than to further limit the scope of protection of the present invention. In the following examples, unless otherwise specified, all raw materials used are commercially available.
[0040] Example 1
[0041] A polymerizable deep eutectic solvent composed of sodium hexafluorophosphate, acrylamide and succinonitrile
[0042] Weigh sodium hexafluorophosphate (NaPF 6 ) 0.34g, succinonitrile (SN) 2.00g, acrylamide (AM) 0.22g are mixed in a reaction reagent bottle, and then stirred at room temperature for 2h to form a clear polymerizable deep eutectic solvent. The appearance of the polymerizable deep eutectic solvent sample is as follows Figure 1 shown.
[0043] Example 2
[0044] This embodiment provides a gel electrolyte prepared based on a polymerizable deep eutectic solvent, which is prepared according to the following method:
[0045] NeA 6 : 0.34g;
[0046] SN: 2.00g;
[0047] AM: 0.22g;
[0048] N,N-dimethylacrylamide (DMA): 0.31 g;
[0049] Fluoroethylene carbonate (FEC): 0.29 g;
[0050] Photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone (PI1173): 0.012 g;
[0051] Step 1: Weigh NaPF 6 , SN, AM and DMA are placed in a container and stirred at room temperature until a clear and transparent liquid is obtained to obtain a polymerizable deep eutectic solvent.
[0052] Step 2: prepare prepolymer solution: weigh FEC as an additive and photoinitiator PI1173, add them into the polymerizable deep eutectic solvent prepared in step 1 and mix them evenly.
[0053] Step 3: Transfer the deep eutectic solvent prepared in step 2 to the mold and complete the polymerization curing by ultraviolet irradiation. The power of the ultraviolet light source is 30W and the irradiation time is 2h. The appearance of the deep eutectic gel electrolyte sample is as follows: Figure 2 shown.
[0054] Example 3
[0055] Preparation of deep eutectic gel electrolyte by homopolymerization of different monomers
[0056] Example 3 was carried out in the same process as Example 2, wherein the polymerizable monomers were AM, DMA, N,N-diethylacrylamide (DEA), and N-isopropylacrylamide (NIPAM), respectively. The deep eutectic gel electrolyte samples homopolymerized with different monomers, the ionic conductivity and oxidation potential at room temperature were shown in Table 1, and the linear sweep voltammetry curve (LSV) was shown in Figure 3 As shown, the oxidation potential of deep eutectic gel electrolytes homopolymerized from different monomers can reach above 4V.
[0057] Table 1. Physicochemical properties of deep eutectic gel electrolyte obtained by homopolymerization of different monomers in Example 3
[0058]
[0059] Example 4
[0060] Preparation of deep eutectic gel electrolyte by copolymerization of different monomers
[0061] Example 4 is carried out in the same process as Example 2, the main difference being that two polymerizable monomers are copolymerized, the first monomer is AM, and the second monomers are DMA, DEA, NIPAM, and 4-acryloylmorpholine (ACMO), respectively. The deep eutectic gel electrolyte samples obtained by copolymerization of different monomers, the ionic conductivity and oxidation potential at room temperature are shown in Table 2, and the LSV is as follows: Figure 4 In the mechanical properties test, the gel electrolyte composed of only AM homopolymer is hard and brittle, the tensile strength of the gel electrolyte composed of only DMA homopolymer is only 13 kPa, while the tensile strength and maximum elongation of the gel electrolyte composed of AM and DMA copolymer are 87 kPa and 1017% ( Figure 5 ). During the stretching of the copolymer gel electrolyte, the polymer-rich phase deforms to dissipate energy by breaking hydrogen bonds, while the solvent-rich phase disperses the stress load, resulting in significantly improved mechanical properties of the copolymer gel. Figure 5 The inset shows the morphology of the copolymerized deep eutectic gel electrolyte before and after folding, and the copolymerized gel has a certain toughness.
[0062] The interfacial compatibility between the electrolyte and the sodium metal anode is a key factor in ensuring the long-term stable cycle of the battery. In order to study the interfacial stability between different electrolytes and the sodium anode, symmetric batteries were assembled using the above three gels as electrolytes and voltage polarization tests were performed. Figure 6 The polarization curves of Na / / Na symmetric cells composed of AM and DMA copolymer gel electrolyte at room temperature are shown. -2 , area capacity 0.1 mAh cm -2 After 1000 hours of continuous operation, there was still no short circuit phenomenon, while the gel electrolyte system composed only of AM homopolymerization only cycled for 190 hours, and the gel electrolyte system composed only of DMA homopolymerization only cycled for 600 hours. Figure 7 The EIS curve of the Na / / Na symmetric battery composed of AM and DMA copolymer gel electrolyte after 1000 cycles, R ct The decrease is attributed to the formation of a stable and uniform SEI film on the surface of sodium metal during the cycle. At the same time, good mechanical properties can effectively inhibit dendrites. Unless otherwise specified below, gel electrolyte generally refers to gel electrolyte copolymerized by AM and DMA.
[0063] Table 2. Physicochemical properties of deep eutectic gel electrolyte obtained by copolymerization of different monomers in Example 3
[0064]
[0065] Example 5
[0066] Deep eutectic gel electrolyte prepared from lithium salt
[0067] Example 5 1.36 g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), 2.28 g of SN, 0.50 g of AM, 0.11 g of DMA, 0.42 g of FEC, and 0.0093 g of PI1173 were weighed and mixed in a reaction reagent bottle, and then stirred at room temperature for 2 h to form a clear polymerizable deep eutectic solvent, and the polymerization was carried out in the same process as in Example 2. The impedance of the deep eutectic gel electrolyte prepared from LiTFSI at room temperature is shown in FIG. Figure 8 As shown, the ionic conductivity is 2.47mS / cm, and the LSV is Fig. 9 As shown, the initial oxidation potential is 4.0V.
[0068] Example 6
[0069] Assembly of Na / / Na symmetric battery and testing of its electrochemical performance
[0070] The positive and negative electrodes in the symmetrical battery are both 14mm sodium sheets. The experimental group uses the deep eutectic gel electrolyte prepared by AM / DMA copolymerization in Example 2. The gel electrolyte directly acts as an electrolyte and a separator without the need for other separators. The control group uses a liquid electrolyte (made of the same proportion of NaPF 6 and SN composed of deep eutectic solvent) and glass fiber diaphragm. The test process was carried out at 0.1mAcm -2 The current density is 0.1 mAh cm -2 The capacity density of the battery was tested by charge and discharge cycle at room temperature. Fig.10 As shown, a comparative analysis of the cycle stability is conducted. The Na / / Na symmetric battery assembled with the deep eutectic gel electrolyte can stably cycle for 1200 h without increasing the polarization voltage, while the liquid battery is short-circuited after cycling for 100 h. The steric hindrance generated by the polymer chain segments can inhibit the side reaction between sodium metal and succinonitrile, indicating that the deep eutectic gel electrolyte prepared in the present invention can improve the cycle stability of the battery.
[0071] Example 7
[0072] Synthesis of Prussian blue HQ-NaFe cathode material and HQ-NaFe / / Na full battery assembly test
[0073] Synthesis of HQ-NaFe: Weigh 2mmol Na 4 Fe(CN) 6 10H 2 O and 1 mL of hydrochloric acid (37%) were added to 100 mL of deionized water, and the mixed solution was stirred at 60°C for 4 h. The solution was allowed to settle for 24 h to obtain HQ-NaFe nanocubes. The HQ-NaFe product was washed three times with deionized water and ethanol by centrifugation, and then dried in a vacuum oven at 100°C for 24 h to obtain the positive electrode material Prussian blue HQ-NaFe.
[0074] Weigh HQ-NaFe: PVDF: SP (weight ratio 80wt%: 10wt%: 10wt%), mix to make a precursor solution, stir mechanically overnight, and dry in a vacuum oven at 90°C for 12h. Cut the positive electrode into 10mm discs and put them into the glove box for later use. Assemble the HQ-NaFe / / Na full battery and perform electrochemical performance tests. Fig.11 The CV curve of HQ-NaFe / / Na assembled from the AM / DMA copolymer gel electrolyte prepared in Example 2, the HQ-NaFe positive electrode, and the sodium sheet negative electrode. HQ-NaFe exhibits a two-electron reaction: cubic cube Rhombus Na 2 Fe II Fe II (CN) 6 It can be observed from the CV curve that multiple reduction peaks appear during the discharge process, indicating that Na + The insertion of ions undergoes a stepwise process. The CV results show that the deep eutectic gel electrolyte provided by the present invention is suitable for Prussian blue / / Na full batteries.
[0075] Example 8
[0076] NFM / / Na full battery assembly test
[0077] Weigh the layered oxide (NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 , referred to as NFM): PVDF: SP (80wt%: 10wt%: 10wt%), mixed to form a precursor solution, mechanically stirred overnight, dried in a vacuum oven at 90°C for 12h, and the positive electrode was cut into 10mm discs and put into a glove box for standby use. Fig.12 The CV curve of the battery assembled with the AM / DMA copolymer gel electrolyte, NFM positive electrode and sodium sheet negative electrode prepared in Example 2. It can be observed from the CV graph that in the Na + There are two pairs of redox peaks in the process of ion insertion / extraction, corresponding to Ni 2+ / Ni 4+ Redox and Fe 3+ / Fe 4+ Redox CV results show that the deep eutectic gel electrolyte provided by the present invention is suitable for NFM / / Na full batteries.
[0078] Example 9
[0079] NVP / / Na full battery assembly test
[0080] Weigh sodium vanadium phosphate (NVP): PVDF: SP (80wt%: 10wt%: 10wt%), mix to form a precursor solution, stir magnetically overnight, dry in a vacuum oven at 90°C for 12h, cut the positive electrode into 10mm discs and put them into a glove box for standby use. The battery assembly process is carried out in an argon atmosphere in the glove box. The inventors further used the deep eutectic gel electrolyte prepared in Example 3 directly as an electrolyte and separator; the control group used a liquid electrolyte (composed of the same proportion of NaPF 6 and SN composed of deep eutectic solvent) and glass fiber separator to assemble NVP / / Na battery. Fig.13 The cyclic voltammetry (CV) curve of the NVP / / Na battery is shown in the figure. It can be seen from the CV curve that the assembled NVP / / Na has an obvious redox peak in the voltage range of 2.5 to 4.0 V. The CV results show that the deep eutectic gel electrolyte provided by the present invention is suitable for NVP / / Na full batteries. Fig.14 The GCD charge-discharge curves of NVP / / Na battery at different currents. When the current density increases from 0.5C to 1C, 2C, and 4C, the discharge specific capacities of NVP / / Na are 110.7, 87.5, 75.2, and 57.3 mAh g, respectively. -1 . Fig.15 Comparison of the cycling performance of NVP / / Na batteries assembled with liquid electrolytes of gel electrolyte at 1C. The NVP / / Na battery assembled with deep eutectic gel electrolyte prepared in Example 3 has a cycling performance of 102.7 mAh g -1 The specific capacity of the battery is 99.5 mAh g after 800 cycles. -1 In contrast, the capacity of the NVP / / Na battery assembled with liquid electrolyte decays rapidly after 150 cycles.
[0081] Example 10
[0082] LFP / / Li full battery assembly test
[0083] Lithium iron phosphate (LFP): PVDF: SP (80wt%: 10wt%: 10wt%) were weighed and mixed to form a precursor solution. The solution was mechanically stirred overnight and dried in a vacuum oven at 90°C for 12h. The positive electrode was cut into 12mm discs and placed in a glove box for later use. Fig.16 The CV curve of the battery assembled with the gel electrolyte, LFP positive electrode and lithium sheet negative electrode prepared in Example 5. + There is a pair of redox peaks in the ion insertion / extraction process, corresponding to the following reactions: LiFePO 4 →Li + +e - +FePO4 The CV results show that the deep eutectic gel electrolyte provided by the present invention is suitable for LFP / / Li full batteries.
Claims
1. A deep eutectic gel electrolyte, characterized in that: The method is obtained by polymerizing a polymerizable monomer-type deep eutectic solvent, and the preparation raw materials include a hydrogen bond acceptor and a hydrogen bond donor, an initiator, and an additive, wherein the hydrogen bond acceptor is a metal salt, and the hydrogen bond donor is succinonitrile and an amide monomer containing an unsaturated double bond.
2. The deep eutectic gel electrolyte according to claim 1, characterized in that: The metal salt hydrogen bond acceptor includes one or more of sodium hexafluorophosphate (NaPF6), sodium perchlorate (NaClO4), sodium bis(trifluoromethanesulfonyl imide) (NaTFSI), sodium bis(fluorosulfonyl imide) (NaFSI), sodium tetrafluoroborate (NaBF4), sodium trifluoromethanesulfonate (NaOTf), sodium nitrate (NaNO3), lithium perchlorate (LiClO4), lithium nitrate (LiNO3), lithium bis(trifluoromethanesulfonyl imide) (LiTFSI), and lithium bis(fluorosulfonyl imide) (LiFSI); the amide monomer hydrogen bond donor containing an unsaturated double bond includes one or more of acrylamide, N-isopropylacrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, and 4-acryloylmorpholine.
3. The deep eutectic gel electrolyte according to claim 1-2, wherein the preparation method comprises the following steps: Step 1: mixing the hydrogen bond acceptor and the hydrogen bond donor in a certain molar ratio, and stirring until clear and transparent, thereby obtaining a polymerizable monomer type deep eutectic solvent; Step 2: Add a small amount of initiator to the solution prepared in step 1 and mix well to obtain a prepolymer solution; Step 3: Pour the prepolymer solution obtained in step 2 into a mold, and then initiate polymerization to obtain a deep eutectic gel electrolyte.
4. The deep eutectic gel electrolyte according to any one of claims 1 to 3, characterized in that: It comprises the following raw material components which are stored independently: a monomeric deep eutectic solvent, an initiator, and an additive; wherein the amount of the initiator is 0.01% to 1% of the molar amount of the hydrogen bond donor; the amount of the additive is 0.1% to 15% of the mass of the monomeric deep eutectic solvent; and the additive is a film-forming additive.
5. The deep eutectic gel electrolyte according to claim 1, characterized in that: The initiator includes a free radical initiator; the initiator includes one or more of 2-oxoglutaric acid, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, and azobisisobutyronitrile; the additive includes fluoroethylene carbonate.
6. The deep eutectic gel electrolyte according to claim 1, characterized in that: The ionic conductivity reaches 1 mS cm at 25 °C -1 above.
7. The deep eutectic gel electrolyte according to any one of claims 1 to 6, characterized in that: Applicable to sodium ion batteries and lithium ion batteries.
Citation Information
Patent Citations
Gel electrolyte based on in-situ polymerization of eutectic solvent system and application
CN116666745A
Preparation method of polyamide-based gel polymer electrolyte with multi-network structure
CN112838262A
Electrolyte and preparation method and application thereof
CN114006030A
Anti-zinc dendrite solid-state zinc-based battery electrolyte and preparation method thereof
CN114122534A
All-solid-state ionic conductive elastomer and preparation method thereof
CN116496443A
Cited By
Self-healing electrolyte for decoupling mechanical strength and conductivity and preparation method of self-healing electrolyte
CN119812444A
Acyl deep eutectic electrolyte and preparation method and application thereof
CN120073062A
High-ionic-conductivity polymer electrolyte with high sodium metal compatibility and preparation method of high-ionic-conductivity polymer electrolyte
CN121812718A
Modified electrolyte, preparation method and application thereof, and alkali metal solid secondary battery
CN122246257A